697 Sleep Quality After COVID-19 Infection. (3rd May 2021) - Hackett, Benjamin; Badami, Varun; Sharma, Sunil; Stansbury, Robert
Abstract: Introduction: COVID-19 has proven to be a novel virus with significant complications to an expanding number of body systems. Hallmark characteristics of COVID-19 include substantial inflammatory response which has been linked to sleep dysregulation in previous studies. We examined the change in sleep quality after acute COVID-19 infections requiring hospitalization. Methods: We performed a retrospective, single-center observational study of 20 patients with acute COVID-19 infection requiring hospitalization. Eligible patients were contacted and completed telephone surveys of the Pittsburgh Sleep Quality Index (PSQI) prior to and 1 month after hospital discharge. A score of ≥5 was indicative of poor sleep quality. Secondary data were collected from EMR. Results: The mean PSQI prior to COVID-19 infection was 6.1, worsening to 10.3 one month after acute infection, denoting a delta-PSQI of 4.2 (p = 0.0004). There were noted statistically significant differences in certain components of the PSQI including: subjective sleep quality 0.8 to 1.7 (delta 0.9, p = 0.0003), sleep latency 1.25 to 1.85 (delta 0.6, p = 0.03), sleep disturbance 1.05 to 1.5 (delta 0.45, p = 0.0009), and daytime dysfunction 0.3 to 1.45 (delta 1.15, p = 0.0005). Sleep latency and daytime dysfunction accounted for the most change. Two groups declared themselves with 6 of the 20 patients having improvement/no change in PSQI, and 14 having worsening. Between these groups certain differences were seen including: Pre-infection PSQI 9.67 vs 4.57 (p = 0.009), delta global PSQI -0.83 vs 6.36 (p < 0.001), delta subjective sleep quality 0.17 vs 1.2 (p = 0.002), delta sleep latency -0.3 vs 1 (p = 0.01), delta sleep duration -0.3 vs 0.93 (p = 0.02), delta sleep efficiency -0.3 vs 0.71 (p = 0.02), and delta daytime dysfunction 0.17 vs 1.57 (p = 0.006). Conclusion: In our study of patients hospitalized for COVID-19 infection specific components of sleep were different following infection. Sleep latency and daytime dysfunction contributed the most to PSQI change. Two groups declared themselves based on PSQI improvement vs worsening. Those with poor sleep prior to infection continued to have poor sleep, while those without prior sleep troubles developed worsened sleep quality. Support (if any):